(untitled) (Clinics, 2015)
OBJECTIVE: The end-tidal concentration of inhalation anesthetics is a clinical indicator for predicting the emergence from anesthesia. This study was conducted to assess the relationship between arterial blood and end-tidal sevoflurane concentrations during emergence. METHODS: Thirty-two female American Society of Anesthesiologists physical status I-II patients receiving general anesthesia for elective gynecologic surgery were included. A fixed dose of 3.5% inspiratory sevoflurane in 6 L min-1 oxygen was maintained until the end of surgery. At 20 and 10 minutes before and 0, 5, 10, 15, and 20 minutes after discontinuing sevoflurane, as well as at the time of eye opening by verbal command, defined as awakening, 1 ml arterial blood was obtained to measure its sevoflurane concentration by gas chromatography. Simultaneous inspiratory and end-tidal concentrations of sevoflurane were detected by an infrared analyzer and tested by Bland-Altman agreement analysis. RESULTS: The arterial blood concentrations of sevoflurane were similar to the simultaneous end-tidal concentrations during emergence: 0.36% (0.10) and 0.36% (0.08) sevoflurane at awakening, respectively. The mean time from discontinuing sevoflurane to eye opening was 15.8 minutes (SD 2.9, range 10-26) and was significantly correlated with the duration of anesthesia (52-192 minutes) (P = 0.006) but not with the body mass index or total fentanyl dose. CONCLUSION: The mean awakening arterial blood concentration of sevoflurane was 0.36%. The time to awakening was prolonged in accordance with the anesthetic duration within 3 hours. With well-assisted ventilation during emergence, the sevoflurane end-tidal concentration was nearly equal to its arterial blood concentration, which could be a feasible predictor for awakening.